Réflexions méthodologiques sur l’analyse phonétique d’un corpus longitudinal et transversal en acquisition du langage - Jérémi Sauvage; Christelle Dodane; Fabrice Hirsch; Melissa Barkat-Defradas (Corela)
The goal of this study is to see whether children’s level of language development has any effect on the acoustic structure of laughter. A major difficulty lies in the fact that such a study needs to combine both synchronic analyses and a longitudinal approach. This paper is based on an acoustic study conducted on 120 laughters produced by 3 monolingual French-speaking children in natural interaction with their environment at the age of 18, 24, 30 and 36 months. Our results are discussed in the context of different methodological issues including: the interests and limitations of shared large corpora, the selection of laughter samples to be analyzed, and the interrelation of quantitative and qualitative approaches.